Traktat w Utrechcie w ocenie wybranych prac XX-wiecznej historiografii brytyjskiej - Lik, Krzysztof (Acta Universitatis Lodziensis. Folia Historica, 2007)
The Utrecht Treaty signed on 11 IV 1713, in fact ending the war of Spanish succesion, turned out to be one of those turning points which finally formed the XVIIl-century Europe and secured an exeptional place in political system of that century fot the British monarchy. No wonder that Utrecht Treaty, and events preceeding it, were the main object of interest in the British historiography for a long time. The period of Queen Anna’s reign, and distinguished people appearing at her court were described by many historians. Unfortunately, those works are not well-known among Polish publicity. The issues of the war of Spanish succesion and the Utrecht Treaty are not the most favourite topics among Polish historians either. For the above reasons Polish reader who want to get some knowledge on that subject may have problems as the only sources of information can be found in textbooks accesible in university libraries and institutes of history. However, it should be stressed that such textbooks are totally different from those we know in our Polish conditions. They are very detailed works presenting both historical knowledge and literary values. It is worth mentioning that among writers who created them were such suberb names as Clark or Trevelyan and they were edited by British best publishing companies like C.U.P., O.U.P. or Longman. In this article one could find live historical books which in my opinion are the most representative for the XXth century British historiography. These are: The Cambridge History o f the British Empire, vol. I, The Old Empire from the Beginings to 1783. G. M. Trevelyan, History of England. The New Cambridge Modern History, vol. VII, The Old Regime. Sir George Clark, The Later Stuarts and Frank O’Gorman, The Long Eighteenth Century.